La motivación como eje articulador para el inter- aprendizaje de la expresión corporal en los estudiantes de 8vo y 9no año de educación básica en la unidad educativa Cuarto Centenario Nº1 de la cuidad de Loja periodo 2013-2014 - Valencia Salinas, José Fabian (2015)
The work investigative is directed to know: the motivation as axis articulator for the inter - learning of the corporal expression in the students of 8vth and 9no year of Basic education, the problematic situation detected in its object that is given by the absence of motivation in the inter - learning of the corporal expression, these factors have a very significant influence in the development of the corporal expression of the students at the moment of developing the expressive and intellectual activities. There is directed to know the suitable motivation skills in inter-learning of the corporal expression in the students of the Educational Unit VI Centenary Nº1. The study categories are: the motivation, inter-learning and the corporal expression. The methodology uses the handlebar of observation like skill and the inductive methods - deductively after the statistician realizes the literary review, the descriptive one, the analytical - synthetic one, to reach the reached information. The results demonstrate the absence of motivation in the pupils and on having applied the proposal, it is satisfactory. In the discussion of reveling empirical strategies used by the teacher. As conclusion, the teacher does not use methodological strategies adapted during the development of inter-learning of the corporal expression. It is recommend deed a training plan prepares it to optimize the pedagogic processes to the teachers of Physical education of the Educational Unit the Fourth Centenary Nº 1 of take care of Loja. The proposal has the purpose of using to the game like motivation skill in inter-learning to achieve a quality education.